Health Care Seeking Interval and Fatality Rate in Swine Flu (H1n1) Epidemic in Surat City - Patel, Prakash B; Patel, Manan J; Prasad, Rachna; Patel, Khushbu; Jadawala, Hiren; Bansal, RK (National Journal of Community Medicine, 2015)
Objectives: This study was conducted to assess influence of reporting time to health care setup on fatality rate in early 2015 swine flu epidemic. Method: All Swine flu positive cases reported to Surat Municipal Corporation (SMC) from Jan to March 2015 were included in the study. Hospital records were studied retrospectively to gather desired information. Results: Incidence rate and fatality rate of swine flu was 16.38 per lac and 5.91% respectively. Mean differences of interval between onsets of symptoms to reporting to hospital is not significant, however lesser interval between onset of symptoms to swab collection and diagnosis of swine flu were significantly associated with lesser fatality. Fatality Rate declines from January to March. Conclusion: After patient report to the health care setup, prompt sample collection and quick diagnosis help to reduce fatality rate.